2004
DOI: 10.1097/01.paf.0000136442.17344.b5
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Suicidal Electrocution

Abstract: Two cases of suicidal electrocution are presented: one using a household lamp, the other using a homemade electrocution machine. The mechanisms of death and the histologic changes in electrocution are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…The cases of SE are very rare (3) and are usually described as incidental or casuistical (3–7). Our previous studies (8,9) revealed an average incidence of 0.09 per 100,000 population per year.…”
Section: Discussionmentioning
confidence: 99%
“…The cases of SE are very rare (3) and are usually described as incidental or casuistical (3–7). Our previous studies (8,9) revealed an average incidence of 0.09 per 100,000 population per year.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocutiontorture cases are also rare. Carelessness, misuse or improper maintenance of electrical equipment represent the chief reasons for non-intentional, electrocution worldwide [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Air embolism has not been described as a mechanism of death in electricity-related deaths [6][7][8]15]. Death from electrocution is usually instantaneous at the time of exposure to the electrical source, due to arrhythmia (ventricular fibrillation), though there are a few reported cases resulting in late deaths associated with electrocution [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying electrophysiological mechanism is disruption of the endogenous electrical polarity of the victim's cells by the exogenous current, causing them to malfunction or cease functioning altogether. These changes ultimately lead to hypoxia and death [6]. In this article, we report an electricity-related death associated with an unusual consequence, air embolism.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation